Sustainable E-Commerce Adoption in Generation Z: The Role of Social Media, Trust, and Digital Literacy on Consumer Behaviour - Vera Sylvia Saragi Sitio; Asti Septinopianti (Jurnal Mirai Management, 2026)
The rapid development of e-commerce in the digital era has created various challenges and opportunities for companies in understanding the factors that affect consumer behavior, especially in Generation Z. This study aims to understand the factors that affect the adoption of sustainable e-commerce in Generation Z, with a focus on the role of social media digital literacy and trust with an exploratory approach that tests the influence of digital literacy, social media, trust, and consumer behaviour using the Partial Least Square Structural Equation Modelling (PLS-SEM) analytical technique. Primary data was used by distributing questionnaires to Generation Z in Jakarta. The population in this study is Generation Z in Jakarta. The sample determination technique used purposive sampling, where the questionnaire was only limited to Gen Z and the number of questionnaires collected amounted to 69 respondents. The results of this study show that digital literacy has a significant influence on consumer behaviour, but does not affect trust. Social media has been proven to have a significant influence on consumer behaviour and trust. Trust does not have a direct or indirect influence on purchase decisions. This study shows that trust as a variable mediator does not show an indirect influence on this study.